Pharmacokinetics and Pharmacodynamics of Garetosmab (Anti‐Activin A): Results From a First‐in‐Human Phase 1 Study. (18th June 2020) - Vanhoutte, Frédéric; Liang, Su; Ruddy, Marcella; Zhao, An; Drewery, Tiera; Wang, Yuhuan; DelGizzi, Richard; Forleo‐Neto, Eduardo; Rajadhyaksha, Manoj; Herman, Gary; Davis, John D.
Abstract: We describe outcomes from the first‐in‐human study of garetosmab (a fully human monoclonal antibody that inhibits activin A) under development for the treatment of fibrodysplasia ossificans progressiva (FOP). In a double‐blind, placebo‐controlled phase 1 study, 40 healthy women of nonchildbearing potential were randomized to receive a single dose of intravenous garetosmab 0.3, 1, 3, or 10 mg/kg; subcutaneous garetosmab 300 mg; or placebo. Serum concentrations of functional garetosmab (with ≥1 arm free to bind to target), total activin A, and antidrug antibodies were measured predose and up to 113 days post–first dose. Garetosmab demonstrated an acceptable safety profile with no dose‐limiting toxicities. Garetosmab displayed nonlinear pharmacokinetics with target‐mediated elimination. With increasing doses of intravenous garetosmab, mean peak concentration increased in a dose‐proportional manner; mean steady‐state estimates ranged from 41.4 to 47.8 mL/kg. A greater than dose‐proportional increase in mean area under the concentration‐time curve from time zero extrapolated to infinity (range, 72.2‐7520 mg*day/L) was observed, consistent with decreasing mean clearance (range, 4.35‐1.34 mL/day/kg). Following administration of intravenous garetosmab, mean concentrations of total activin A increased in a dose‐dependent manner. At 10 mg/kg, total activin A levels reached a state of little or no change between weeks 4 and 12, suggesting saturation of the target‐mediated pathway. No safety signals were seen in this study to preclude investigation in patients. Following intravenous administration, garetosmab concentrations decreased quickly, then decreased over time (reflecting linear elimination), and finally decreased in a nonlinear phase, reflecting target‐mediated elimination. Results here support further investigation. Garetosmab 10 mg/kg every 4 weeks intravenously is being evaluated in patients with FOP (NCT03188666).